A Retrospective Analysis of the Effect of Anlotinib in Patients With Lung Cancer With or Without Previous Antiangiogenic Therapy - Suo, Jiaojiao; Sun, Yu; Fu, Yan; Xiu, Weigang; Zhang, Xuanwei; Wang, Yan; Zhu, Jiang (Frontiers in Oncology, 2021)
Objective The purpose of this study was to initially investigate the effect of previous antiangiogenic therapy (bevacizumab and endostatin) on the efficacy of anlotinib in patients with advanced or metastatic lung cancer (LC). Methods We retrospectively collected the clinical data of patients with LC treated with anlotinib and divided them into group A (treated with anlotinib after the failure of previous antiangiogenic drugs and group B (no prior use of antiangiogenic drugs). We used propensity score matching (PSM) for confounding factors between the groups. Progression-free survival (PFS) and overall survival (OS) were also recorded. Results A total of 160 patients were included in the analysis. The median OS in groups A and group B was 11.8 months and 16.1 months (P=0.120), whereas the median PFS was 3.1 months and 4.7 months (P=0.009), respectively. Moreover, the objective response rate (ORR) of the two groups was 9.6% and 10.4% (P=0.874), and the disease control rate (DCR) was 71.1 % and 80.5% (P=0.165). After PSM (n=46), baseline characteristics were comparable between groups A and B. Furthermore, the median OS of the two groups was 14.6 months and 16.2 months (P=0.320), whereas the median PFS was 3.5 months and 4.5 months (P=0.040), respectively. Moreover, the ORR of the two groups were 13.0% and 10.9% (P=0.748), and the DCR were 78.3% and 82.6% (P=0.599), respectively. Conclusions Previous antiangiogenic treatments may affect the PFS of patients who receive anlotinib later, but it might not affect the patient’s ORR and OS.